2015
DOI: 10.1007/s11418-015-0939-z
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of Yinhuapinggan granule against influenza virus infection in the ICR mice model

Abstract: Yinhuapinggan granule (YHPG), a Chinese medicine granule based on Ma-Huang-Tang (Ephedra Decoction) and the clinical experience of Professor Wan Haitong, is used in traditional Chinese medicine (TCM) for the treatment of colds, influenza, fever, inflammation and cough. This study investigated the antiviral effects of YHPG on the production of inflammatory cytokines in influenza virus (IFV)-infected mice and evaluated the effect of YHPG on the expression of NF-κB p65 and the level of key signaling molecules in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Biomed Res 2018 Special Issue S424 Special Section:Medical Diagnosis and Study of Biomedical Imaging Systems and Applications based on Ma Huang Tang, has antiviral effects in IFV-infected mice, which is associated with the inhibition of the TLR4-MyD88-TRAF6 signal pathway. The results cited thus far indicate that TCM has a very well antiviral effect [20]. These findings suggest that YQP serum intervention groups decreased the expression of TLR4/MyD88/TRAF-6 and TLR3/ TRAM/TRIF pathway, especially in 3min groups and 6 min High-dose group.…”
Section: Discussionmentioning
confidence: 70%
“…Biomed Res 2018 Special Issue S424 Special Section:Medical Diagnosis and Study of Biomedical Imaging Systems and Applications based on Ma Huang Tang, has antiviral effects in IFV-infected mice, which is associated with the inhibition of the TLR4-MyD88-TRAF6 signal pathway. The results cited thus far indicate that TCM has a very well antiviral effect [20]. These findings suggest that YQP serum intervention groups decreased the expression of TLR4/MyD88/TRAF-6 and TLR3/ TRAM/TRIF pathway, especially in 3min groups and 6 min High-dose group.…”
Section: Discussionmentioning
confidence: 70%
“…Our previous studies have demonstrated that YHPG has obvious antiviral, anti-inflammatory and antitussive effects in mice and rats [17][18][19][20]. The HPLC analysis clearly revealed the presence of the major constituents of YHPG (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Previous researches have shown that YHPG has distinct antitussive, antiinflammatory and antibacterial effects (He et al 2014;Wan et al 2016). Further, antiviral studies has demonstrated that YHPG has significant effects on ameliorating influenza virus-induced inflammation, inhibiting TLRs/MyD88 mediated NF-jB signalling pathway, and inhibiting influenza virus replication (Peng et al 2016a(Peng et al , 2016b. However, the antiviral effects and its possible mechanism of YHPG in the apoptosis signalling pathway are still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…According to the traditional dose ratio of 4 (Radix Puerariae Lobatae): 4 (Flos Lonicerae Japonicae): 4 (Polygoni Cuspidati Rhizoma): 2 (Ephedrae Herba): 2 (Armeniacae Semen Amarum): 1 (Glycyrrhizae Radix) ( Supplementary Table 1), YHPG granules were prepared by water-extraction and ethanol-precipitation, and the quality control of YHPG was also performed by HPLC, as reported in our previous research. HPLC analysis was carried out at 210 nm for the determination of eight active components in YHPG, containing L-ephedrine (0.73 mg/g), D-pseudoephedrine (0.407 mg/g), chlorogenic acid (1.92 mg/g), amygdalin (6.37 mg/g), puerarin (4.35 mg/g), polydatin (1.79 mg/g), glycyrrhizic acid (0.692 mg/g) and emodin (0.329 mg/g), respectively (Supplementary Figure 1) (Peng et al 2016a(Peng et al , 2016b.…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation